Compositional and provenance changes of paleocene sandstones in the eastern cordillera and western side of the Maracaibo block (2009)
In the eastern cordillera of Colombia and western of Maracaibo block, paleocene sandy units show significant compositional and provenance differences, suggesting either changes in the tectonic regimen in the source areas or in depositional conditions. Lower paleocene units show a decrease of total lithic fraction from Usme to Tunja, whereas significatively increases in the Catatumbo and Cesar Basin (total lithic fraction 20%-50%). For the upper paleocene units, in all the studied localities there is an increase in the total lithic fragments (between 35%- 60%), being Usme, Medina, and the Cesar - Ranchería basins, the areas with the highest values. Source areas for detritus in Bogotá and Cesar - Ranchería include volcanic and metamorphic rocks (Central cordillera, SNSM). In the axial eastern cordillera, the principal source area consists of a sedimentary cover. In Medina, and the axial part of the east cordillera remains the question about the provenance of metamorphic fragments, whereas metamorphic fragments recorded in the Catatumbo basin may come from the Santander Massif. The constant content of metamorphic lithic fragments in paleocene units, and the mixing with feldspars and volcanic fragments in some areas, are topics that need further study. Other methods are necessary to complete the existing information for better understanding about the provenance of paleocene units in the studied zones.